Diagenesis and reservoir quality of Neoproterozoic dolomitized microbialites following multi-stage diagenetic fluid activity: a case study of the Sinian Dengying Formation, China - Dong, Shuyi; Fu, Meiyan; Song, Rongcai; Guo, Hengwei; Shen, Qiuyuan (Frontiers in Earth Science, 2023)
Neoproterozoic marine microbialites have been targets for exploration and hydrocarbon reservoir development. The original depositional fabric and diagenesis control the pore systems of microbialites, leading to the complicated origin of microbialite reservoirs. This study aimed to reveal the origin of microbialite reservoirs following multi-stage diagenetic fluid activity in the fourth Member of the Dengying Formation in the central Sichuan Basin in southwestern China. The fourth Member of the Sinian Dengying Formation developed dolomitized microbialites, mainly including stromatolites, laminates, and thrombolites. Based on the background of tectonic movement, petrology and geochemistry examinations were executed to analyze the origin of the microbialite reservoir. Based on the cathodoluminescence and the homogenization temperature of the brine inclusions, it is credible that there were four stages of diagenetic fluid activities in the burial diagenesis. In the first stage, the microbialite reservoir was charged by oil in the Silurian period, with evidence from residual asphalt around the pores. In the second stage, dolomite precipitated to incompletely fill the pore spaces. In the third stage, the silica-rich diagenetic fluid with high temperature resulted in the precipitation of authigenic quartz. In the last stage, the oil charged again during the Triassic period, followed by siliceous filling, with residual asphalt filling the pore spaces. There were two stages of subaerial emergence, which occurred in two episodes of the Sinian-Early Cambrian Tongwan movement. The evidence for the two tectonic events includes two phases of dolomites with meteoric water origin, two cycles of V, Sr, and Na element profiles, two instances of negative excursion δ18O isotope, and two cavity layers. By comparison, the karstification of reservoirs in the Tongwan III episode could generate a higher quality of reservoir than that in the Tongwan II episode. As a result, the quality of the microbialite reservoir from the fourth Member of the Dengying Formation was mainly improved by the subaerial exposure in the Tongwan III episode and then was partly destroyed by the siliceous filling. The identification of multi-staged diagenetic fluid charging can illustrate the evolution of the reservoir quality of Neoproterozoic microbialites.